PERANCANGAN PROGRAM APLIKASI PENJUALAN DAN KOMPARASI PRODUK PADA OIL & WINE COMPUTER - Rocky Christy (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
PT. OIL AND WINE is an enterprise web store which is engaged in the sale of IT goods like gadgets, computers, laptops, and its various accessories. PT. OIL AND WINE has a vision to be the most advanced and integrated web store that allows visitors to its website in online transactions conveniently and safely. The purpose of this application is a program design to improve existing business processes within the company so that the company can achieve the maximum benefit. In addition, the design of application programs is also to facilitate the customer in selecting the required product. With this application program, companies can improve business processes effectively and efficiently. This application is designed to be easy to use (user friendly), so that every customer who visits this website is not difficult to choose the product and buy the desired product. Key WordsOil & Wine, Website,Web